1970
DOI: 10.1083/jcb.45.1.158
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Changes in Cells of Pea Embryo Radicles During Germination

Abstract: Radicles (I mm long) of pea embryo axes, excised from dormant seeds and from seeds soaked for 80 min, 8, 12, and 48 hr, were fixed in glutaraldehyde and postfixed in OSO4 . The nucleus was only slightly changed by 48 hr soaking, but cytoplasmic organelles underwent developmental changes . There was proliferation of endoplasmic reticulum, the appearance of dictyosomes, and an inward migration of lipid bodies . Most of these changes were observed within 8 hr after soaking started . Plastids, mitochondria, protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
7

Year Published

1973
1973
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 31 publications
4
30
0
7
Order By: Relevance
“…during germination, and perhaps also during dehydration. A similar association has previously been noted, for example, in plastids of elongating pollen tubes (Larson, 1965) and in radicles of germinating Pisum sativum (Perner, 1965;Yoo, 1970). E.R.…”
Section: Discussionmentioning
confidence: 71%
“…during germination, and perhaps also during dehydration. A similar association has previously been noted, for example, in plastids of elongating pollen tubes (Larson, 1965) and in radicles of germinating Pisum sativum (Perner, 1965;Yoo, 1970). E.R.…”
Section: Discussionmentioning
confidence: 71%
“…The cytoplasm contains free ribosomes, but few or no free polysomes can be detected. The mitochondria have a simplified structure with an electronopaque matrix and few cristae (1,7,8,11,17). The respiration rate of air-dry seeds has been measured manometrically in a respirometer and is of the order of 100 ul h-' g-' dry weight (Qo2Qco.).…”
mentioning
confidence: 99%
“…Single-membranes were also reported for lipid bodies in pea seeds (Yoo, 1970) and lipid storage vacuoles in the cotyledons of Cucurbita maxima (Lott et al, 1971). …”
Section: Membranementioning
confidence: 99%
“…The data suggested either that the plasma and plastid membranes become similar (in the sense that they bind or attract the composite lipid); or that two classes of composite lipid vesicles exist such that one class binds to the plasma membrane, and the other binds to the plastid membrane. In another study, lipid bodies in pea seeds were found closely packed against each other and confined to regions near the cell surface or near plastids in radicles of dormant, 80 minute, 8 and 12 hour embryos (Yoo, 1970). Sorokin and Sorokin (1966) reported that in tissues from Campanula persicifolia L., spherosomes were distributed throughout the tissue and appeared singly, in twos or in more numerous groupings.…”
Section: Membranementioning
confidence: 99%
See 1 more Smart Citation